Intrathoracic versus Cervical ANastomosis after minimally invasive esophagectomy for esophageal cancer: study protocol of the ICAN randomized controlled trial. Issue 1 (December 2016) - van Workum, Frans; Bouwense, Stefan; Luyer, Misha; Nieuwenhuijzen, Grard; Peet, Donald; Daams, Freek; Kouwenhoven, Ewout; van Det, Marc; van den Wildenberg, Frits; Polat, Fatih; Gisbertz, Suzanne; Henegouwen, Mark; et al.
Abstract Background Currently, a cervical esophagogastric anastomosis (CEA) is often performed after minimally invasive esophagectomy (MIE). However, the CEA is associated with a considerable incidence of anastomotic leakage requiring reintervention or reoperation and moderate functional results. An intrathoracic esophagogastric anastomosis (IEA) might reduce the incidence of anastomotic leakage, improve functional results and reduce costs. The objective of the ICAN trial is to compare anastomotic leakage and postoperative morbidity, mortality, quality of life and cost-effectiveness between CEA and IEA after MIE. Methods/design The ICAN trial is an open randomized controlled multicentre superiority trial, comparing CEA (control group) with IEA (intervention group) after MIE. All patients with esophageal cancer planning to undergo curative MIE are considered for inclusion. A total of 200 patients will be included in the study and randomized between the groups in a 1:1 ratio. The primary outcome is anastomotic leakage requiring reintervention or reoperation, and secondary outcomes are (amongst others) other postoperative complications, new onset of organ failure, length of stay, mortality, benign strictures requiring dilatation, quality of life and cost-effectiveness. Discussion We hypothesize that an IEA after MIE is associated with a lower incidence of anastomotic leakage requiring reintervention or reoperation than a CEA. The trial is also designed to give answers to additional research questions regarding a possible difference in functional outcome, quality of life and cost-effectiveness. Trial registration Netherlands Trial Register:NTR4333 . Registered on 23 December 2013.